77 NOVEL MECHANISM OF PROSTAGLANDIN E2-MEDIATED ENDOTHELIAL CELL BARRIER ENHANCEMENT: ROLE OF EPCR, S1P1 RECEPTOR, EPAC, RAP1, AF-6, AND PROFILIN. (1st March 2006) - Singleton, P. A.; Dore, S.; Garcia, J. G.N.
Abstract : Prostaglandin E2 (PGE2 ) is an important tissue-specific autocrine inflammatory mediator. In lung, unlike other tissues, PGE2 exerts an anti-inflammatory, tissue-reparative, and endothelial cell (EC) barrier protective response, which can have therapeutic potential in various pulmonary diseases. Therefore, we examined the mechanism of PGE2 -induced pulmonary EC barrier regulation. Addition of PGE2 (100 nM, 5-30 minutes) to EC induced recruitment of EP2 and EP3 receptor (E prostanoid receptor subtypes), EPCR (endothelial cell protein C receptor), S1P1 receptor, Epac (cAMP-activated Rap1 exchange factor), Rap1 (small GTP binding protein), AF-6 (scaffolding protein that binds activated Rap1 and profilin), and profilin (actin polymerizing cytoskeletal protein) to caveolin-enriched microdomains (lipid rafts). Silencing EP2 (but not EP3), EPCR (siRNA) or inhibiting adenylyl cyclase activity (29, 59-dideoxy-39-ATP) attenuated PGE2 -induced recruitment of Epac and Rap1 to EC lipid rafts. Silencing S1P1 receptor inhibited PGE2 -induced AF-6 and profilin recruitment to EC lipid rafts. Finally, inhibiting lipid raft formation (methyl-b-cyclodextrin), inhibiting adenylyl cyclase activity, or silencing EP2, EPCR, S1P1 receptor, Epac, Rap1, AF-6, or profilin attenuated PGE2 -induced increased EC barrier function. Taken together, these data suggest that PGE2 ligation of EP2 receptor induces EPCR and S1P1 receptor signaling required for Epac, Rap1, AF-6, and profilin recruitment to lipid rafts during pulmonary EC barrier enhancement.